Marketing Strategy for New Venture in Information Technology Education (Online Tutorial – TUTON) - Lubis, Esty Hutami Dewi; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
Indonesia has a rapid development in Information Technology (IT) as well as the public interest to learn it. However, to find qualified employee in IT is difficult, they often lacks proper education in IT background. IT education is not only need quality, but also follow current trends. Some negative opinions always appear in description of online education. First, Indonesian online tutorial customer had always assumed that what is available on the internet is free. Second, it is hard to get customer interest without quality customer expected. Third, the customers who will be interested of online education are university students that lack of fund. Further analysis needed in order to find the root cause of these problems.The root cause analysis used SWOT analysis that employ PEST Factor Analysis, Porter’s 5 Forces Analysis and Concept Testing result..The root cause analysis concludes that the TUTON product as online education is not strong enough to face the market. It needs new research and analysis of marketing mix.The objectives of TUTON based on the root causes are developing competitive products and promoting paid tutorial. Marketing strategies are needed to achieve these objectives. The strategies are explained with 4Ps Marketing Mix and Porter’s Generic Competitive Strategies. TUTON main marketing strategies points are make tutorial with video media (Product), focus on tutorial making (Product), consider a new distribution place (Place, Pricing), the website hosting size will be reduced (Place, Pricing), and use YouTube as promotion media (Promotion) and the differentiation strategy is use video as tutorial media.Reduced website hosting size strategy had been implemented to TUTON. Other strategies implementation will be done in this year from May 2013 to January 2014. If all the marketing strategies implemented are going well within budget and time allocation, TUTON will achieve the objectives.